Development of a validated framework to describe and evaluate community-based rehabilitation practice in Chinese communities - Chung, Eva Yin-han (Curtin University, 2009)
Community-based rehabilitation (CBR) is defined as "a strategy within general community development for rehabilitation, equalization of opportunities and social inclusion of all children and adults with disabilities" (ILO, UNESCO and WHO, 2004, p.2). The overall objective is "to ensure that people with disabilities are able to maximize their physical and mental abilities, have access to regular services and opportunities, and to become active contributors to the community" (ILO, UNESCO and WHO, 2004, p.3). A second objective is to "activate communities to promote and protect the human rights of people with disabilities through changes within the community, for example, by removing barriers to participation" (ILO, UNESCO and WHO, 2004, p.3). CBR is a common strategy employed in different countries for promoting inclusion and participation for people with disabilities. It has been evolving for nearly three decades and its practice varies in different contexts.The Chinese government has included the strategy to promote "rehabilitation for all" in their eleventh five-year plan. Many CBR programs have emerged in Chinese communities since the 1980s. Most programs adopted Western CBR concepts but also found their own way to succeed and survive in the local communities. However, there is no validated way to measure and assure the quality and performance of a CBR program. Consequently, cost-effectiveness of programs also cannot be confirmed. Moreover, the uniqueness of Chinese culture and background make it difficult to transfer the Western concepts and practice of CBR into Chinese communities.The primary aim of this study was to develop a validated framework that could effectively evaluate the quality of CBR practice in Chinese communities. This study adopted a case study approach to build and validate a framework. It comprised three phases: (1) to develop and test an initial framework, (2) to refine the framework into a CBR Evaluation Framework, and (3) to test the validity of the CBR Evaluation Framework.The aim of Phase I was to define the core elements of CBR. An Initial Framework was first built based on a review of seven conceptual papers regarding CBR evaluation. This Initial Framework was then verified with examples of CBR programs cited in thirteen published journal articles. Again using the case study approach, the Initial Framework was tested in five real Chinese CBR programs. Missing elements were added and necessary modifications were made to form a Revised Framework.Phase II added a measurement scale using types of evidence found in Chinese CBR programs to measure the quality of core elements and domains in the Framework. A qualitative methodology was used to identity possible types of evidence to support best practice in the five Chinese CBR programs. Themes regarding levels of evidence for best practice were then compared with the International Audit Standards on Audit Evidence. With core elements defined in Phase I and measurement scales delineated in Phase II, the Framework was then refined into the CBR Evaluation Framework.Phase III further tested the utility and the convergent construct validity of the CBR Evaluation Framework. The content validity of the CBR Evaluation Framework was tested by applying the Framework to twelve rehabilitation programs in Chinese communities to demonstrate the utility of the Framework in describing and differentiating rehabilitation programs of different natures. Convergent construct validity was tested by correlating the results generated from the CBR Evaluation Framework and that of the Most Signification Change technique (MSC) in the four best practice Chinese CBR programs.The main result of this study was the establishment of a validated CBR Evaluation Framework of five domains, twenty-five elements and seventy-two outcome indicators. This CBR Evaluation Framework demonstrated that it was able to describe the twelve studied programs and differentiate five types of community programs: (1) rehabilitation programs of narrow focus, (2) rehabilitation programs of broad focus, (3) premature CBR programs, (4) growing CBR programs, and (5) mature CBR programs. Convergent construct validity testing showed a strong and significant correlation with the results obtained using MSC in the four best practice programs.Another result of this study was the exploration of successful outcomes of CBR in Chinese communities. Using the CBR Evaluation Framework, successful outcomes of the Chinese CBR practice in the five domains were documented. Successful outcomes of elements in Domains One and Two were mostly reported by the studied programs. The psychosocial element and the involvement of family members were found to be the elements most commonly found in Chinese CBR programs.This research resulted in a validated Framework for describing and measuring quality in CBR practice in Chinese communities. This Framework provides local government, funders, managers and workers with a comprehensive evaluation to document and measure quality and performance. Quality of programs is expected to be further enhanced and documented through using this framework.